2020
DOI: 10.1590/2177-9465-ean-2019-0148
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs related to oral antidiabetic use among individuals with diabetes

Abstract: Objective: To identify beliefs related to oral antidiabetic use among individuals with type 2 diabetes mellitus, based on the Theory of Planned Behavior. Method: This is a descriptive, quantitative and qualitative study conducted with 32 participants using oral antidiabetic drugs. Data was collected through an open question tool and analyzed by number of emissions and content. Results: Among the behavioral beliefs, the following stand out: (a) as an advantage, to keep diabetes controlled; and (b) as disadvan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Four themes on how “social influences” affect diabetes management were identified in 40 studies (66.7%) [ 27 29 , 31 , 32 , 35 , 37 , 39 47 , 49 , 51 – 53 , 57 , 59 – 62 , 64 67 , 70 , 73 77 , 79 , 81 , 83 – 85 ]: lack of and support from family and friends, social gatherings, stigma and peer support. More than half of the studies described that family and friends’ support is a fundamental piece in the management of the disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four themes on how “social influences” affect diabetes management were identified in 40 studies (66.7%) [ 27 29 , 31 , 32 , 35 , 37 , 39 47 , 49 , 51 – 53 , 57 , 59 – 62 , 64 67 , 70 , 73 77 , 79 , 81 , 83 – 85 ]: lack of and support from family and friends, social gatherings, stigma and peer support. More than half of the studies described that family and friends’ support is a fundamental piece in the management of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Along a similar line, regarding “beliefs about capabilities ” 6 studies identified issues with patients not feeling capable of controlling the disease, for example, not being able to inject insulin correctly [ 27 , 32 , 65 , 77 , 78 , 86 ]. The domain “memory , attention , and decision processes” was applied in 8 studies [ 27 , 33 , 37 , 43 , 47 , 62 , 82 , 86 ], and “intentions” (4 studies) [ 31 , 47 , 53 , 80 , 82 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Guénette and et al., presented adherence to medication associated with having signs to remember to take them [ 39 ], Gouveia also reported that forgetting to take medication in patient with type 2 diabetes was not a barrier of adherence because it was perceived as an unaware behavior by patients; however, if this behavior was repeated it could be on purpose. At this stage, patient paid little attention to take their medications [ 40 ]. Most of the patients had taken their anti-diabetic medicines the previous day.…”
Section: Discussionmentioning
confidence: 99%